Clostridium difficile-associated diarrhoea. Issue 877 (November 1998) - Wight, N.; Curtis, H.; Hyde, J.; Borriello, S. P.; Mahida, Y. R.
Abstract : At our hospital, the number of cases of Clostridium difficile-associated diarrhoea increased from 29 in 1993 to 210 in 1995. The case notes of 110 patients with C difficile-associated diarrhoea during the first 6 months of 1995 were analysed retrospectively. The majority of the patients (106) had received antibiotics before the onset of diarrhoea; 46 had received three or more different antibiotics and 28 had received metronidazole. In 19 patients, the first stool sample after the onset of diarrhoea was negative for C difficile cytotoxin, with a mean delay of 8.2 days before a positive stool sample. We conclude that C difficile-associated diarrhoea was associated with the usage of multiple antibiotics, and that metronidazole did not protect against colonisation by C difficile. We also recommend that more than one stool sample should be tested for the C difficile cytotoxin.